Logistics and Freight Services : Policies to Facilitate Trade - Rastogi, Cordula; Arvis, Jean-Francois (Washington, DC: World Bank, 2020)
The disruption to logistics and freight networks endangers trade and distribution of essential goods to combat the crisis and foster the recovery. Governments should work in coordination with logistics and retail industry, with a view to ensure continuity of shipping, air, trucking, and warehousing capacities at critical gateways and hubs and along trade corridors. The short-term response by governments and the private sector must go beyond addressing the immediate crisis and draw out the path towards economic resilience of the sector. Countries should also coordinate with key trading partners at the sub-regional or international level on policies such as increased e-services at ports and green express lanes for truckers. Countries should not install additional controls on transit commerce. Instead, border control and inspections should be streamlined and harmonized, based on international standards. To manage and ensure functioning of essential transport services, firms can use fewer workers and follow social distancing and other good health practices.